Response and adaptation of the transcriptional heat shock response to pressure - Coffin, Carleton H.; Fisher, Luke A.; Crippen, Sara; Demers, Phoebe; Bartlett, Douglas H.; Royer, Catherine A. (Frontiers in Microbiology, 2024)
IntroductionThe molecular mechanisms underlying pressure adaptation remain largely unexplored, despite their significance for understanding biological adaptation and improving sterilization methods in the food and beverage industry. The heat shock response leads to a global stabilization of the proteome. Prior research suggested that the heat shock regulon may exhibit a transcriptional response to high-pressure stress.MethodsIn this study, we investigated the pressure-dependent heat shock response in E. coli strains using plasmid-borne green fluorescent protein (GFP) promoter fusions and fluorescence fluctuation microscopy.ResultsWe quantitatively confirm that key heat shock genes-rpoH, rpoE, dnaK, and groEL - are transcriptionally upregulated following pressure shock in both piezosensitive Escherichia coli and a more piezotolerant laboratory-evolved strain, AN62. Our quantitative imaging results provide the first single cell resolution measurements for both the heat shock and pressure shock transcriptional responses, revealing not only the magnitude of the responses, but also the biological variance involved. Moreover, our results demonstrate distinct responses in the pressure-adapted strain. Specifically, PgroEL is upregulated more than PdnaK in AN62, while the reverse is true in the parental strain. Furthermore, unlike in the parental strain, the pressure-induced upregulation of PrpoE is highly stochastic in strain AN62, consistent with a strong feedback mechanism and suggesting that RpoE could act as a pressure sensor.DiscussionDespite its capacity to grow at pressures up to 62 MPa, the AN62 genome shows minimal mutations, with notable single nucleotide substitutions in genes of the transcriptionally important b subunit of RNA polymerase and the Rho terminator. In particular, the mutation in RNAP is one of a cluster of mutations known to confer rifampicin resistance to E. coli via modification of RNAP pausing and termination efficiency. The observed differences in the pressure and heat shock responses between the parental MG1655 strain and the pressure-adapted strain AN62 could arise in part from functional differences in their RNAP molecules.